2016
DOI: 10.1007/s00253-016-8000-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure within an activated sludge reactor added with phenolic compounds

Abstract: Biodegradation of phenolic compounds in bioreactors is well documented, but the changes in the bacterial populations dynamics during degradation were not that often. A glass bubble column used as reactor was inoculated with activated sludge, spiked with 2-chlorophenol, phenol and m-cresol after 28 days and maintained for an additional 56 days, while the 16S rRNA gene from metagenomic DNA was monitored. Proteobacteria (68.1%) dominated the inoculum, but the bacterial composition changed rapidly. The relative ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this sense, sequences M3, M22, M23, and M25 were related to an uncultured actinobacterium , an Acidobacteria bacterium, a Salinibacterium xinjiangense , and an Actinobacterium , respectively. These species have been found in bacterial communities of activated sludge reactors fed with phenolic compounds 50 or of wastewater treatment in SBR reactors with low concentrations of 4‐CP (1.5 mg L −1 ) 49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, sequences M3, M22, M23, and M25 were related to an uncultured actinobacterium , an Acidobacteria bacterium, a Salinibacterium xinjiangense , and an Actinobacterium , respectively. These species have been found in bacterial communities of activated sludge reactors fed with phenolic compounds 50 or of wastewater treatment in SBR reactors with low concentrations of 4‐CP (1.5 mg L −1 ) 49 …”
Section: Resultsmentioning
confidence: 99%
“…In this sense, sequences M3, M22, M23, and M25 were related to an uncultured actinobacterium, an Acidobacteria bacterium, a Salinibacterium xinjiangense, and an Actinobacterium, respectively. These species have been found in bacterial communities of activated sludge reactors fed with phenolic compounds 50 or of wastewater treatment in SBR reactors with low concentrations of 4-CP (1.5 mg L −1 ). 49 According to the above, 2-CP could be consumed by heterotrophic and/or by ammonium-oxidizing species through the AMO participation, since they remained present in most of the operating cycles in both reactors, even with the increase in the concentration of 2-CP.…”
mentioning
confidence: 99%
“…Again, to our knowledge, no direct links between this bacterial genus and PBDE exposures in wildlife or in experimental studies could be found in the literature. It had been observed that certain Actinobacteria have a strong ability to utilize phenolic compounds in bioreactors and wastewater treatment plants (Gómez-Acata et al, 2016;Baskaran et al, 2017). These phenolic compounds may include products derived from the degradation or enzyme-mediated biotransformation of PBDEs.…”
Section: Correlations Between Contaminants and The Sle Beluga Skin Mi...mentioning
confidence: 99%
“…Phenol can alter the microbial community structure in manmade ecosystems (Gomez-Acata et al 2017;Pereira et al 2014;Poirier et al 2016;Wu et al 2019). But the shift in bacterial community structure in natural ecosystems induced by phenol is still unknown.…”
Section: Effects Of Phenol On Sediment Bacterial Community Structurementioning
confidence: 99%